Réponses

2013-10-07T10:02:41+02:00
2x²-3x-4=2((x-3/4)²-41/16)
2x²-3x-4=2(x²-6/4x+9/16-41/16)
2x²-3x-4=2x²+12/4+18/16-82/16
2x²-2x²-3x=12/4+18/16-82/16+4
-3x=48/16+18/16-82/16+64/16
-3x=48/16
-3x=3
x= -1
merci mais je dois démontrer que c est 2 équations sont égales, je ne recherche pas la valeur de x
merci pour votre aide
2013-10-07T11:04:05+02:00
F(x) = 2x² -3x -3 -4 = 2 ((x-3/4)²-41/16)
f(x) =2x²-3x-4=2(x² +9/16 -41/16)
f(x) = 2x²-3x - 4= 2x² +18/16 - 41/16
f(x) = 2x²-2x²-3x = +4 +18/16 -41/16
f(x) = -3x = +16 /16+18/16 -41/16
f(x) = -3x = -7/16